2004
DOI: 10.1038/sj.gene.6364136
|View full text |Cite
|
Sign up to set email alerts
|

TNF and TNFR polymorphisms in severe sepsis and septic shock: a prospective multicentre study

Abstract: Tumour necrosis factor (TNF) is an important pro-inflammatory cytokine produced in sepsis. Studies examining the association of individual TNF single nucleotide polymorphisms with sepsis have produced conflicting results. This study investigated whether common polymorphisms of the TNF locus and the two receptor genes, TNFRSF1A and TNFRSF1B, influence circulating levels of encoded proteins, and whether individual polymorphisms or extended haplotypes of these genes are associated with susceptibility, severity of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
63
4
3

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(83 citation statements)
references
References 58 publications
(79 reference statements)
13
63
4
3
Order By: Relevance
“…In agreement with a recent epidemiological study in a Brazilian hospital in the state of Paraná, we found that the main medical cause for ICU admission was sepsis (35% against 40% in Kauss et al 29 recent study), and the mortality rates at ICU plus follow-up were 46% in our study compared to 42% in Kauss et al 29 Our study revealed no association between -308G > A TNF-α genotypes and adverse outcomes (sepsis, septic shock, higher organ dysfunction or mortality) from critical illness. Our results demonstrated that the -308A rare allele frequency was 15%, confirming the trend documented in Danish (22%), 24 English (20%), 23 French (18%), 17 and Spanish subjects (9%). 30 The -308A allele has higher level of inducible and constitutional TNF-α, 13,14 but its phenotypical effects in sepsis, septic shock, organ dysfunction, and mortality have been contradictory; 31 while it was perceived in some genetic association studies; 16,18 in other it was not present.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…In agreement with a recent epidemiological study in a Brazilian hospital in the state of Paraná, we found that the main medical cause for ICU admission was sepsis (35% against 40% in Kauss et al 29 recent study), and the mortality rates at ICU plus follow-up were 46% in our study compared to 42% in Kauss et al 29 Our study revealed no association between -308G > A TNF-α genotypes and adverse outcomes (sepsis, septic shock, higher organ dysfunction or mortality) from critical illness. Our results demonstrated that the -308A rare allele frequency was 15%, confirming the trend documented in Danish (22%), 24 English (20%), 23 French (18%), 17 and Spanish subjects (9%). 30 The -308A allele has higher level of inducible and constitutional TNF-α, 13,14 but its phenotypical effects in sepsis, septic shock, organ dysfunction, and mortality have been contradictory; 31 while it was perceived in some genetic association studies; 16,18 in other it was not present.…”
Section: Discussionsupporting
confidence: 76%
“…30 The -308A allele has higher level of inducible and constitutional TNF-α, 13,14 but its phenotypical effects in sepsis, septic shock, organ dysfunction, and mortality have been contradictory; 31 while it was perceived in some genetic association studies; 16,18 in other it was not present. [22][23][24] Specifically, in contrast to our study (n = 520, southern Brazilian population), positive associations between -308A allele and sepsis, septic shock, higher organ dysfunction, and/or mortality were found when Mira et al 17 (n = 89, France), Tang et al 18 (n = 112, China), O'Keefe et al…”
Section: Discussioncontrasting
confidence: 50%
See 1 more Smart Citation
“…This has been seen in other complex diseases, such as the discovery of a single nucleotide polymorphism (SNP) in complement factor H as a risk factor for macular degeneration (13). In AKI, genetic variation in inflammatory cytokines such as Tumor Necrosis Factor-alpha (TNF-␣) and Interleukin-6 (IL-6) have recently been proposed as risk factors (11,(14)(15)(16)(17). This is due to the role of inflammatory mediators in the pathophysiology of AKI, especially with ischemia and sepsis (1,18,19).…”
mentioning
confidence: 99%
“…Other studies demonstrating an association of "high-secretor" genotypes and more severe disease include children with meningococcal infections [95] and bacteremia [90], severe sepsis in adults [26,83,85,96], and community acquired pneumonia in adults [97,98]. However, these results have not been uniformly observed [28,[99][100][101][102][103], and further studies are needed. Thus, individuals in which genetic variations result in a hyper-response during sepsis (as with those with the TNF--308A allele) or hypo-response (as with those with the TNF--238A allele) may have worse outcomes with sepsis.…”
Section: Tumor Necrosis Factor (Tnf-)mentioning
confidence: 70%